Potentially inappropriate prescribing for adults with diabetes mellitus: a scoping review protocol. Issue 7 (14th July 2020) - Ayalew, Mohammed B.; Dieberg, Gudrun; Quirk, Frances; Spark, M. Joy
ABSTRACT: Objective: This scoping review aims to explore and map studies investigating potentially inappropriate prescribing (PIP) for adults with diabetes mellitus. Introduction: Inappropriate prescribing for people with diabetes mellitus has been reported by various authors focusing on different aspects of inappropriateness. A preliminary search revealed no published reviews on PIP for adults with diabetes mellitus. As a result, it is difficult to obtain a comprehensive map of PIP in this patient group. Inclusion criteria: This scoping review will consider all studies on PIP for adults with the diagnosis of type 1 or type 2 diabetes mellitus from any clinical setting. Studies conducted in pediatric populations or in adults with pre-diabetes or gestational diabetes will be excluded. Methods: A three-step search strategy (i.e. an initial limited search in PubMed and ProQuest Central databases, a main search of eight databases and gray literature, and manual searches of reference lists of included articles) will be utilized. No language restrictions will be applied. All retrieved articles will be screened against the inclusion/exclusion criteria at title, abstract, and full-text stages. Data to be extracted from each study will include, but not be limited to, country, objective, study population, study methodology, type of PIP studied, examples of PIP events, medications involved, and criteria used for PIP identification. Data will be extracted by study team members using an online application for conducting systematic synthesis of evidence.